Development and Validation of UV Spectroscopic Method for the Quantification of Telmisartan in Bulk and Marketed Formulations - Yegnoor Anand Kumar; Ambika Muttal; G hemalatha; Neeladri Srinivasulu (Asian Journal of Pharmaceutical Research and Development, 2025)
Two new simple and accurate solvent blends have been presented for the quantification of Telmisartan (TEL) in bulk and its tablet dosage form. The developed analytical method was validated and established in ICH Q2 (R1). Telmisartan exhibit 298 nm and 291 nm for Solvent A, Solvent B respectively and found was linear for a range of 1 µg/ml to 50 µg/ml.The goodness of fit study suggests good correlation coefficient R2 - 0.9989 and 0.999 for proposed solvents. The validity of Beer’s law with intercept response < 2% calculated by the least square method indicating functional linearity between the concentration of analyte and the absorbance. The (LOD) of Telmisartan was found to be 0.07642±0.1224μg/ml and the limit of quantification (LOQ) of Telmisartan was found to be 0.07642±0.1224μg/ml with %RSD < 2.The analytical method validation of proposed solvent blends was performed by carrying out precision and accuracy studies. The Accuracy percentage recovery on three different levels i.e. 50%, 100% and 150% was found to be within the acceptable limits with RSD < 2. The proposed solvent blends were validated for specificity, precision, ruggedness, accuracy and robustness. Overall study suggest that the proposed solvent blends can be used for quantification of Telmisartan in bulk and its tablet dosage form and can be applied for the everyday quality control analysis.